Crude Tall Oil based Renewable Diesel: Performance, Emission Characteristics and Storage Stability - Spoof-Tuomi, Kirsi; Vauhkonen, Ville; Niemi, Seppo; Ovaska, Teemu; Lehtonen, Vilja; Heikkilä, Sonja; Nilsson, Olav (SAE International, 2021)
International policies aiming at replacing fossil fuels with bio-components are getting stronger. Hydrotreating of bio-oils is a sustainable way to produce premium quality diesel fuels from completely renewable feedstocks. The Finnish forestry company UPM has developed an innovative production process based on hydrotreatment to convert crude tall oil (CTO) into a high-quality renewable diesel fuel that can be used as a blending component or as 100% fuel in all diesel engines without modifications. Paraffinic, high cetane CTO renewable diesel allows efficient and clean combustion, reducing harmful air emissions in addition to not releasing any new CO2 into the atmosphere during their combustion. This study investigated the effect of CTO renewable diesel (BVO) on engine performance and exhaust emissions. Conventional market diesel served as a reference fuel. The research engine was a common-rail off-road diesel engine, operated by using the load points of the non-road steady state cycle C1 of the ISO8178 standard. The use of BVO reduced all regulated gaseous emissions (NOx -10%, CO -7%, HC -7%). A significant 26% reduction was obtained in cycle-weighted particulate number. In addition to low emissions, fuels are required to remain stable and of high quality even after long-term storage. Another target of the present study was to clarify the influence of long-term storage on CTO renewable diesel properties. In this context, the paper reports the comprehensive results of fuel analyses in a fresh state and after four years of storage, the focus being on parameters that may be affected by the formation of oxidation products. BVO did not show substantial storage stability problems.
Keywords: Exhaust emissions; Diesel / compression ignition engines; Diesel fuels; Combustion and combustion processes; Storage; Engines; Particulate matter (PM); Agricultural vehicles and equipment; emissions; fi=Energiatekniikka|en=Energy Technology|